TRANSCRANIAL DIRECT CURRENT STIMULATION AND MANUAL ASYMMETRIES: THE EFFECT OF THE STIMULATION ON THE MANUAL DEXTERITY - Mayndra Giusti Salvador; Herbert Ugrinowitsch; Marco Aurélio Romano-Silva; Débora Marques de Miranda; Tércio Apolinário-Souza; Guilherme Menezes Lage (Journal of Physical Education)
ABSTRACT The aim of this study was to evaluate the effect of transcranial direct-current stimulation (tDCS) on the primary motor cortex (M1) in the manual performance asymmetries in a manual dexterity tasks. The sample consisted of 28 volunteers, right-handed, men and without neurological impairment. The task (Grooved Pegboard) consisted of inserting 25 pins in 25 receptacles, as soon as possible. The task was executed in the pretest with both hands to define the level of manual asymmetry. tDCS or Sham were applied a week after the pretest, then the subjects were evaluated in the post-test. The results revealed that the effects of tDCS in M1 did not reduce asymmetries in a manual dexterity task. However, only the tDCS group improved the performance from pretest to the posttest (p <0.05) in both hands. Stimulation of the right M1 may have generated benefits in the contralateral M1.